The Evangelists in Clement's "Hypotyposes" - Stevens, Luke J. ca. 20./21. Jh. (Journal of early Christian studies, 2018)
Excerpts from Clement of Alexandria's lost Hypotyposes recounting the scribal activities of the evangelists Mark, Luke, and John puzzlingly differ despite overlapping in content. Actually, what little Clement said of the writing of Mark's Gospel and of Hebrews is preserved in the Adumbrations, while Eusebius of Caesarea knew the Hypotyposes only through an intermediary given to embellishing paraphrase; furthermore, the claim by John of Scythopolis that Clement ascribed the Dialogue of Papiscus and Jason to Luke arose from a misplaced note on Hebrews. An additional point in the Hypotyposes is hypothesized ascribing the compilation of the Pauline corpus to Luke.